راس مال الأسرة و اثره على التحصيل التربوي و الصحي للطفل المتمدرس دراسة ميدانية بالمدرسة الابتدائية قدوري عبد القادر بقرية بواد الليل ولاية الاغواط - درافة بن خدة; دلاسي امحمد (My University, 2023)
Today, the world has become dependent on material things and focuses its interests on economics, including economic capital as a refresher and resource for society in general, and on the family in particular, because it has become in control of its various and diverse needs and the needs of its children, which in turn reflect the educational and health status. For the child, and reflects the health care he receives, and this is either negatively or positively in light of the living situation and the material conditions that each family goes through, and therefore the economic environment of the family has an important place because of the roles it plays with the school in order to achieve the aspirations .of the family in achieving good academic and health for the schooling child Keywords: capital, family, academic achievement, health